Tanggung Jawab Suez Canal Authority Pada Peristiwa Terblokirnya Terusan Suez Tahun 2021 - Ida Nur Azizah (Faculty of Law, Universitas Airlangga, 2024)
The Suez Canal is one of the most important artificial waterways for international trade by sea. The blockage of the Suez Canal in 2021 due to the shipwreck of the Ever Given dealt a heavy blow to the global economy. This study examines the legal status of the Suez Canal and the responsibility of the Suez Canal Authority for the blocking of the Suez Canal so that if there will a similar event in the future, this research can be used as legal reference. This thesis is a doctrinal research with a statutory approach and a conceptual approach. According to the provisions of the United Nations Convention on the Law of the Sea 1982, the legal status of the Suez Canal is inland waters. This status was followed by the function of the Suez Canal as an international waterways. The obligation of the Suez Canal Authority to navigate the Suez Canal is demonstrated by the implementation of the pilotage activities assigned to the Ever Given on the day the Suez Canal was blocked. Guidance by the pilot is the responsibility of the captain of the ship because he acts in the interests of the ship